2010
DOI: 10.1007/s11172-010-0384-9
|View full text |Cite
|
Sign up to set email alerts
|

Directed synthesis and immunoactive properties of (2-hydroxyethyl)ammonium salts of 1-R-indol-3-ylsulfanyl(sulfonyl)alkanecarboxylic acids

Abstract: A general method for the synthesis of 1 alkyl(allyl)(benzyl) substituted (indol 3 yl) sulfanylalkanecarboxylic acids and hexane 1,6 diyl(1,4 phenylenemethylene)bisindol 3 yl sulfanylalkanecarboxylic acids from the corresponding N substituted indoles and bisindoles, thiourea, iodine, and halogencarboxylic acids was developed. The oxidation of substituted (indol 3 yl)sulfanylalkanecarboxylic acids for the first time afforded their analogs containing the sulfonyl group. New (2 hydroxyethyl)ammonium salts of 1 R i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…The structures of compounds 1-5 were proved by IR, 1 H, 13 С, and 15 N NMR techniques and their compositions were confirmed by elemental analysis. The crystal structure of tris-(2-hydroxyethyl)ammonium indol-3-ylsulfanylacetate 1 was established by X-ray diffraction analysis.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The structures of compounds 1-5 were proved by IR, 1 H, 13 С, and 15 N NMR techniques and their compositions were confirmed by elemental analysis. The crystal structure of tris-(2-hydroxyethyl)ammonium indol-3-ylsulfanylacetate 1 was established by X-ray diffraction analysis.…”
Section: Discussionmentioning
confidence: 96%
“…Results of preliminary screening of anti-proliferative activity of compounds 2-5 were shown in [13]. To expand this study we examined the immunodeppressive action of compounds 1-5 in a consistent approach and their toxicity.…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that salicylic acid is widely used in cosmetology and medicine due to its antiseptic action. Based on the papers [14][15][16][17][18], it can be expected that triethanolammonium salicylate would have a similar effect. We …”
Section: The Influence On Growth Properties Of the Fungus Rhizopus Ormentioning
confidence: 99%
“…A number of studies have shown [14][15][16][17][18] that many protatranes have biological activity, which is mainly determined by the atrane structure of the cation and the nature of an anion. The first compound of this class was triethanolammonium salt of 2-methylphenyloxyacetic acid [2-CH 3 C 6 H 4 OCH 2 COO] -[NH(CH 2 CH 2 OH) 3 ] + (trecrezan), which is a drug of wide spectrum of action (adaptogen, immunomodulator, etc.)…”
Section: Introductionmentioning
confidence: 99%